2011
DOI: 10.2174/092986711798347270
|View full text |Cite
|
Sign up to set email alerts
|

Using Feature Selection Technique for Drug-Target Interaction Networks Prediction

Abstract: Elucidating the interaction relationship between target proteins and all drugs is critical for the discovery of new drug targets. However, it is a big challenge to integrate and optimize different feature information into one single "knowledge view" for drug-target interaction prediction. In this article, a feature selection method was proposed to rank the original feature sets. Then, an improved bipartite learning graph method was used to predict four types of drug-target datasets based on the optimized featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Many published papers have demonstrated that the optimized features could improve predictive accuracy [1925]. For high-dimension data, some features are noise or redundant information which has negative contribution to the prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Many published papers have demonstrated that the optimized features could improve predictive accuracy [1925]. For high-dimension data, some features are noise or redundant information which has negative contribution to the prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Using the same approach, we identified new genetic determinants that play important functional roles in the thermostable proteins [ 31 ], halostable proteins [ 32 ], and P1B-ATPase heavy metal transporters [ 21 ]. Furthermore, feature selection techniques and other learning methods such as bipartite learning graph and semi-supervised algorithms have already been used in drug-target interactions and the capability of these methods in predicting drug-target datasets has been proven [ 33 ]. In the present study, we used the same strategy to evaluate correlation between HCV gene attributes at nucleotide levels with treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Dimensionality reduction: These techniques like PCA and t-Distributed Stochastic Neighbor Embedding (t-SNE) help visualize and interpret complex pharmacological datasets by transforming high-dimensional data into lower-dimensional representations while preserving essential information. They aid in better understanding and decision-making [64][65][66][67][68][69][70].…”
Section: Feature Selection and Dimensionality Reduction Techniquesmentioning
confidence: 99%